Instant Game for Facebook and Mobile - Ásgeir Einarsson 1986-; Bergur Páll Gylfason 1988-; Daði Magnússon 1988-; Vignir Jónsson 1988- (2011)
Þetta er lokaskýrsla verkefnisins en hún er ein af 12 skjölum, sem skilað var vegna verkefnisins. Þau er hægt að nálgast á CD-diski á bókasafni Háskólans í Reykjavík. We are developing an Instant game that is written against Betware IGF (Instant Game Framework). Instant Game is a gambling game where the outcome is predetermined. All reusable code will go into a separate package (framework) which can be used to develop new games more easily. The game is written in JavaScript and uses the benefits of HTML5. Unlike Flash games there is support for HTML5 and JavaScript on Apple‘s mobile devices (iPad, iPhone). The game will run in all major browsers and scale well between devices. The game can also make use of Facebook features. Betware